2021
DOI: 10.1002/er.6656
|View full text |Cite
|
Sign up to set email alerts
|

Impact of optimal power generation scheduling for operating cleaner hybrid power systems with energy storage

Abstract: De-carbonization of the electric power system, reduction in greenhouse gas emissions and the enhancement of environmental security have emphasized the need for the optimal utilization of renewable/cleaner energy in power system operation. However, unpredictability and intermittency are the major barriers that limit the penetration of renewable power generation (RPG). In this context, large-scale energy storage (LSES) facilities may prove to be an effective means for mitigating the long-term volatility and vuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Another approach to ease meeting the limitations of RESs variability is to use the complementarity between various RESs [21], i.e., two or more energy sources with complementary availability periods such as PV and WT [11]. Many studies have reported the merits of complementarity of various RESs in various countries such as Italy [22] and Canada [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another approach to ease meeting the limitations of RESs variability is to use the complementarity between various RESs [21], i.e., two or more energy sources with complementary availability periods such as PV and WT [11]. Many studies have reported the merits of complementarity of various RESs in various countries such as Italy [22] and Canada [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The security and reliability of modern power system is prime concern of present electric utility 1 . Several unwanted phenomena leads to instabilities in power system.…”
Section: Introductionmentioning
confidence: 99%
“…The ESSs deployment beside RESs can be pointed as a favorable solution for managing the uncertainties associated with RESs in energy systems 22 . The ESSs help the conventional generating units in the ramping process when a generation shortage or overdo is occurred 23‐25 . In this way, the application of ESS units in the energy system's security enhancement is underlined as one of the most interesting fields of study 26‐28 .…”
Section: Introductionmentioning
confidence: 99%
“…22 The ESSs help the conventional generating units in the ramping process when a generation shortage or overdo is occurred. [23][24][25] In this way, the application of ESS units in the energy system's security enhancement is underlined as one of the most interesting fields of study. [26][27][28] In Reference 26, the presence of distributed ESS (DESS) is reflected in the SCOPF problem.…”
Section: Introductionmentioning
confidence: 99%